CONTENT AND METHODS OF FORMING THE CREATIVITY OF FUTURE TEACHERS ABOUT ENERGY - Jumayev Axrom Asror o‘g‘li (American Journals Publishing, 2024)
The article provides information on the content and methods of forming creative thinking in future energy engineers. The PISA (The Program for International Student Assessment) international assessment program outlines the basic concepts of the direction of creative thinking assessment, important aspects to be focused on and assessment approaches.
Keywords: PISA, The Program for International Student Assessment assessment, approaches, ability, competence, research, analysis, creative assignments.